1985
DOI: 10.2307/20094743
|View full text |Cite
|
Sign up to set email alerts
|

Semen Characteristics in a Captive Mithun (Bos frontalis)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…A previous study [15] reported mean semen volume collected with a transrectal massage in beef bulls was 2-6 ml (1-9 ml). Lesser volume had been reported in Mithun as reported [7] which only 0.75 ml. Colors of the semen samples in this study were not different compared to the previous study in banteng [1,2].…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…A previous study [15] reported mean semen volume collected with a transrectal massage in beef bulls was 2-6 ml (1-9 ml). Lesser volume had been reported in Mithun as reported [7] which only 0.75 ml. Colors of the semen samples in this study were not different compared to the previous study in banteng [1,2].…”
Section: Resultsmentioning
confidence: 62%
“…Besides, this original protocol needs dummy cow or female to perform. On the other hand, transrectal massage had been used as semen collection in several animals closely related to banteng, which were Mithun and gaur [7,8]. This method is considered to be easier and simpler to perform since it needs no expensive tool like electro ejaculator, dummy cow or female presence and needs a shorter time to train.…”
Section: Introductionmentioning
confidence: 99%